Penerapan Metode NaÃ¯ve Bayes untuk Prediksi Minat Baca Berdasarkan Usia - Lis Utari; Yawmil Ulfah (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
Reading is one of the activities favored by all circles of society, and a place that can be visited for reading activities is the library. One of them is the Pajajaran Sports Hall Library, based on the data obtained from more than 100 visitors who come to visit the Pajajaran Sports Hall Library each year. However, visitors who borrow do not necessarily have a high reading interest. In this study, an application was made that can predict library visitors who have a high reading interest. In order to predict future reading interest using the method Naive Bayes. It uses variables obtained from borrowing data and carried out preprocessing and obtained several variables used to make predictions, namely name, book category, number of late days, age group, and level of reading interest. This is done to predict the reading interest of visitors to the Pajajaran GOR Library, who have a high level of reading interest and a low level of reading interest. So that the librarian can find out the level of reading interest of the visitors, and the collection of books in the Pajajaran GOR Library can be increased based on the preferred book category of all ages. The accuracy test has also been carried out using the formula confusion matrix with an accuracy value of 80%, which means that the application that has been made is suitable for use.